Perceived frequency of pharmacist-led drug counseling and its association with patient satisfaction in pharmaceutical installations - Dian Meiliani Yulis (Lembaga Edukasi Ilmiah Indonesia, 2026)
Introduction: Pharmacist-led drug counseling is a core component of pharmaceutical care and plays an important role in supporting rational medicine use and patient-centered services. Variations in the frequency of counseling provided in pharmaceutical installations may influence how patients perceive service quality and satisfaction. Methods: A quantitative cross-sectional study was conducted among 60 patients receiving pharmaceutical services in pharmaceutical installations. Data were collected using a structured questionnaire measuring patients’ perceptions of the frequency of pharmacist-led drug counseling and their level of satisfaction. Descriptive statistics and Pearson correlation analysis were applied using statistical software. Results: The findings showed that patients generally perceived drug counseling to be provided frequently and reported a high level of satisfaction with pharmaceutical services. A statistically significant positive correlation was identified between perceived counseling frequency and patient satisfaction, indicating that more frequent counseling was associated with higher satisfaction levels. Conclusion: Frequent pharmacist-led drug counseling contributes positively to patient satisfaction in pharmaceutical installations and should be strengthened as part of quality improvement efforts in pharmaceutical care